Mechanism of Yinqin Oral Liquid in the Treatment of Chronic Pharyngitis Based on Network Pharmacology - Ji S; Xu F; Zhu R; Wang C; Guo D; Jiang Y (Dove Medical Press, 2021)
Shiliang Ji,1 Fei Xu,2 Ruifang Zhu,1 Cheng Wang,2,3 Dongkai Guo,1 Yiguo Jiang1 1Laboratory of Clinical Pharmacy, The Affiliated Suzhou Science and Technology Town Hospital of Nanjing Medical University, Suzhou, People's Republic of China; 2College of Pharmacy, Nanjing Medical University, Nanjing, People's Republic of China; 3The Health Supervision Institute of Suzhou High-Tech Zone, Suzhou, People's Republic of ChinaCorrespondence: Dongkai Guo; Yiguo JiangLaboratory of Clinical Pharmacy, The Affiliated Suzhou Science and Technology Town Hospital of Nanjing Medical University, No. 1 Li Jiang Road, High-Tech District, Suzhou, 215153, People's Republic of ChinaTel +86-512-69584330Fax +86-512-69584513Email dongkaiguo@126.com; jiangyiguo0515@126.comBackground: Yinqin oral liquid (YOL) has curative effect for upper respiratory tract infections, especially for chronic pharyngitis (CP). Since the traditional Chinese herbal formulae are complicated, the pharmacological mechanism of YOL remains unclear. The aim of this work was to explore the active ingredients and mechanisms of YOL against CP.Methods: First, the profile of putative target of YOL was predicted based on structural and functional similarities of all available YOL components, which were obtained from the Drug Bank database, to the known drugs using TCMSP. The chemical constituents and targets of honeysuckle, scutellaria, bupleurum and cicada were searched by TCMSP, CTD, GeneCards and other databases were used to query the CP-related genes, which were searched by UniProt database. Thereafter, the interactions network between compounds and overlapping genes was constructed, visualized, and analyzed by Cytoscape software. Finally, pathway enrichment analysis of overlapping genes was carried out on Database for Annotation, Visualization, and Integrated Discovery (DAVID) platform.Results: The pathway enrichment analysis showed 55 compounds and 113 corresponding targets in the compound-target network, and the key targets involved PTGS1, ESR2, GSK3β, NCOA2, ESR1. The PPI core network contained 30 proteins, including VEGFA, IL6, ESR1, RELA and HIF1A. A total of 148 GO items were obtained (p< 0.05), 102 entries on biological process (BP), 34 entries on biological process (BP) and 12 entries on cell composition (CC) were included. A total of 46 signaling pathways were obtained by KEGG pathway enrichment screening (p< 0.05), involving cancer, PI3K-AKT, hepatitis, proteoglycans, p53, HIF-1 signaling pathways.Conclusion: These results collectively indicate YOL (including the main ingredients luteolin and baicalein) as a highly effective therapeutic agent for anti-inflammation, through the NF-kB pathway.Keywords: Yinqin oral liquid, chronic pharyngitis, network pharmacology, NF-kB, multi-target analysis